The Role of Islamic Cultural History Teachers in Improving Student Learning Activities through the Cooperative Learning Method in Class XI Aat State Islamic Senior High School 4 Tabalong - Hatmiah Hatmiah (Integrated Education Journal, 2026)
This research is motivated by the increasing activeness of class XI A students of MAN 4 Tabalong in learning Islamic cultural history in 2025 through the cooperative learning method. This method is believed to be able to increase the active involvement of students and deepen the understanding of Islamic cultural history material through cooperative activities in groups. This study aims to determine the role of Islamic cultural history teachers in increasing student learning activities through cooperative learning methods in learning Islamic cultural history in class XI A MAN 4 Tabalong and the factors that influence the role of Islamic cultural history teachers in increasing student learning activities through cooperative learning methods in learning Islamic cultural history in class XI A MAN 4 Tabalong. This study is a field study using a qualitative descriptive approach. The informants included the principal, Islamic cultural history subject teachers, substitute Islamic cultural history teachers, and students in class XI A at MAN 4 Tabalong. Class XI A was chosen as the research object due to its high enthusiasm for learning, stable learning patterns, and responsive and cooperative students. Data collection techniques included observation, interviews with Islamic cultural history teachers, documentation, and data analysis, including data reduction, data presentation, and drawing conclusions. Based on the research findings, Islamic cultural history teachers have diverse roles in carrying out their duties and responsibilities. These roles have been proven to increase student engagement in Islamic cultural history learning. Teachers not only deliver material but also facilitate meaningful learning experiences and encourage active student involvement in discussions and group work. This finding aligns with constructivism theory, which asserts that knowledge is actively constructed through social interaction. This increased learning activity is influenced by both internal and external factors. However, both factors have the potential to become obstacles if not handled properly, and therefore need to be addressed to ensure optimal learning.